Modeling and Optimization of Printed Spiral Coils in Air, Saline, and Muscle Tissue Environments - Jow, Uei-Ming (2009)
Printed spiral coils (PSCs) are viable candidates for near-field wireless power transmission to the next generation of high-performance neuroprosthetic devices with extreme size constraints, which will target intraocular and intracranial spaces. Optimizing the PSC geometries to maximize the power transfer efficiency of the wireless link is imperative to reduce the size of the external energy source, heating of the tissue, and interference with other devices. Implantable devices need to be hermetically sealed in biocompatible materials and placed in a conductive environment with high permittivity (tissue), which can affect the PSC characteristics. We have constructed a detailed model that includes the effects of the surrounding environment on the PSC parasitic components and eventually on the power transfer efficiency. We have combined this model with an iterative design method that starts with a set of realistic design constraints and ends with the optimal PSC geometries. We applied our design methodology to optimize the wireless link of a 1-cm(2) implantable device example, operating at 13.56 MHz. Measurement results showed that optimized PSC pairs, coated with 0.3 mm of silicone, achieved 72.2%, 51.8%, and 30.8% efficiencies at a face-to-face relative distance of 10 mm in air, saline, and muscle, respectively. The PSC, which was optimized for air, could only bear 40.8% and 21.8% efficiencies in saline and muscle, respectively, showing that by including the PSC tissue environment in the design process the result can be more than a 9% improvement in the power transfer efficiency.